2013
DOI: 10.1120/jacmp.v14i3.4269
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric‐modulated arc therapy for the treatment of a large planning target volume in thoracic esophageal cancer

Abstract: Recently, volumetric‐modulated arc therapy (VMAT) has demonstrated the ability to deliver radiation dose precisely and accurately with a shorter delivery time compared to conventional intensity‐modulated fixed‐field treatment (IMRT). We applied the hypothesis of VMAT technique for the treatment of thoracic esophageal carcinoma to determine superior or equivalent conformal dose coverage for a large thoracic esophageal planning target volume (PTV) with superior or equivalent sparing of organs‐at‐risk (OARs) dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 20 publications
(21 reference statements)
3
25
0
Order By: Relevance
“…Similar to published literature, D95 in this study was comparable between VMAT and IMRT plans ( P > 0.5); however, CI was statistically improved in favor of VMAT ( P < 0.001). The target volumes in this study, however, were significantly larger than reported by others.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to published literature, D95 in this study was comparable between VMAT and IMRT plans ( P > 0.5); however, CI was statistically improved in favor of VMAT ( P < 0.001). The target volumes in this study, however, were significantly larger than reported by others.…”
Section: Discussionsupporting
confidence: 92%
“…Improvement in target dose delivery and reduction of dose to OARs with IMRT compared with 3D‐CRT has been established . VMAT is an improved and more efficient method of delivering IMRT as demonstrated for other tumor sites . A single feasibility study investigating the use of VMAT for treatment of RPS is reported; however, they did not perform a direct comparison of VMAT to IMRT as it has been done for other tumor sites.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggested that V 5 [1114], V 10 [12, 14, 15], and MLD [14, 15, 17, 18] were correlated with radiation pneumonitis, although the determination of the contributors to radiation pneumonitis was challenging, since a variety of treatment/patient-related factors appeared to influence this risk.…”
Section: Discussionmentioning
confidence: 99%
“…There were several studies demonstrating that VMAT could reduce delivery time and MUs compared with IMRT [1215]. Reduction of delivery time could decrease the possibility of the intrafraction patient motion that leads to target underdosage and/or worse OARs sparing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation